Technological Activation of Building Envelopes to Achieve Environmental Comfort (Journal of Engineering, 2025)
With the rapid advancement of construction technologies, the architectural envelope of a building has evolved beyond a mere structural element into an integrated system designed to achieve comprehensive environmental comfort by controlling thermal, lighting, and acoustic factors within architectural spaces. This research focuses on the technological activation of building envelopes through modern innovations such as smart glass, adaptive walls, natural ventilation systems, and advanced insulation technologies, all of which contribute to enhancing building performance and promoting sustainability. The study explores key concepts and strategies related to the performance of building envelopes and examines how artificial intelligence, the Internet of Things, and smart materials can enhance energy efficiency while improving user comfort. Additionally, it reviews contemporary architectural applications that have successfully implemented innovative solutions in smart envelope design. Findings indicate that integrating dynamic shading technologies, smart ventilation systems, and phase-changing materials significantly reduces energy consumption and enhances indoor environmental quality. These strategies offer a sustainable solution for achieving environmental comfort in future buildings.